2019
DOI: 10.25165/j.ijabe.20191203.4310
|View full text |Cite
|
Sign up to set email alerts
|

Overview of emerging technologies in sprinkler irrigation to optimize crop production

Abstract: Water saving is an essential part of sprinkler irrigation owing to the impact of climate change and rising energy costs. This review highlights the technologies that are emerging in sprinkler irrigation to optimize crop production. While there have been notable advances in irrigation, the continued progress has occurred by the combination of current status with the postulation of new ideas such as conversion of high-pressure sprinkler to low-pressure ones, incorporation of smart controllers in sprinkler irriga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Furthermore, the precise application of fertilizers through point placement reduces fertilizer requirements and enhances FUE and energetics by maximising crop nutrient uptake ( Shafagh et al, 2008 ; Nayak et al., 2019 ; Gebre and Earl, 2021 ). Studies have reported that sprinkler irrigation will enhance the WUE of the crops by 20%–30% and saves water by 30%–45% ( Zhao et al, 2009 ; Li et al., 2019 ; Solgi et al., 2022 ). Nevertheless, most of the studies focus on yield and soil fertility status wherein there is not much focus on basic physiological relationships, which finally defines the yield of crop.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the precise application of fertilizers through point placement reduces fertilizer requirements and enhances FUE and energetics by maximising crop nutrient uptake ( Shafagh et al, 2008 ; Nayak et al., 2019 ; Gebre and Earl, 2021 ). Studies have reported that sprinkler irrigation will enhance the WUE of the crops by 20%–30% and saves water by 30%–45% ( Zhao et al, 2009 ; Li et al., 2019 ; Solgi et al., 2022 ). Nevertheless, most of the studies focus on yield and soil fertility status wherein there is not much focus on basic physiological relationships, which finally defines the yield of crop.…”
Section: Introductionmentioning
confidence: 99%
“…With the automated technology of irrigation, human intervention can be reduced [75,76]. Some advantages of this innovation can be discussed as follows.…”
Section: Advantages Of Automated Sprinkler Irrigationmentioning
confidence: 99%
“…It poses challenges to most large-scale overhead phenotype platforms. Consequently, our primary focus lies in the development of compact, agile, and side-view-capable phenotyping robots as the optimal solution [5,[23][24][25] . In order to better reduce the size of the robot and reduce the cost of experiment time, we should also choose efficient computer vision models to match smaller edge devices.…”
Section: Introductionmentioning
confidence: 99%